PERSUASIVE AND EDUCATIVE ADVERTISING CONTENT OF QUICK RESPONSE CODE INDONESIAN STANDARD IN PANDEMIC ERA - Kristanti, Evelyn; Marta, Rustono Farady (Universitas Pendidikan Ganesha, 2021)
The digital payment system had increased rapidly, especially when Corona Virus Disease (COVID-19) entered Indonesia. Increasing technological advances have shifted people's preference towards cashless transaction activities. These days, money is known to have spread viruses such as COVID-19. In order to support the National Economic Recovery program, Bank Indonesia (BI) developed Contactless QRIS, which allows users to make contactless payments with merchants during the COVID-19 pandemic. BI positions its products in the eyes of consumers by using the internet and YouTube social media as a platform that plays a vital role in framing society's paradigm towards a reality, thus influencing people's attitudes. The research problem is aimed to know and analyze the content analysis of advertising